2017
DOI: 10.1088/1755-1315/80/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Bond characteristics of reinforcing steel embedded in geopolymer concrete

Abstract: Abstract. The force transferring between reinforcing steel and the surrounding concrete in reinforced concrete is influenced by several factors. Whereas, the study on bond behaviour of geopolymer concrete (GPC) is lagging. In this paper, an experimental attempt has been made to evaluate the geopolymer concrete bond with reinforcing steel of different diameter and embedded length using standard pull out test. The geopolymer concrete is made of ground granulated blast furnace slag (GGBFS) as geopolymer source ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It was noted that bond stress reduced by about 5.5% with increasing embedment length for all CRAC mixes, as applied load was distributed over a larger surface area with an increasing embedment length. In the existing literature, Kathrival et al [44] and Kim and Park [45] also reported a reduction in bond stress with increasing embedment length for varying percentages of replacement.…”
Section: Influence Of Embedment Lengthmentioning
confidence: 94%
See 1 more Smart Citation
“…It was noted that bond stress reduced by about 5.5% with increasing embedment length for all CRAC mixes, as applied load was distributed over a larger surface area with an increasing embedment length. In the existing literature, Kathrival et al [44] and Kim and Park [45] also reported a reduction in bond stress with increasing embedment length for varying percentages of replacement.…”
Section: Influence Of Embedment Lengthmentioning
confidence: 94%
“…Similarly, the bond stress was decreased by 7.84%, 10.82%, 5.49%, 13.81%, and 17.65%, respectively, for CRAC mixes prepared with N100-R0, N75-R25, N50-R50, N25-R75, and N0-R100 and an embedment length of 6đť‘‘ . Sarker [14], Romanazzi et al [25], Kathrival et al [44], and Kim and Park [45] reported that bond stress was decreased with the increasing diameter of the steel bar. This was attributed to the larger contact surface area between the reinforcing steel bar and the surrounding concrete, resulting in a distribution of the load over a larger contact area and consequently resulting in a reduction in bond stress.…”
Section: Influence Of Bar Diametermentioning
confidence: 99%